Australian general practitioners' preferences for managing the care of people diagnosed with cancer. Issue 2 (26th December 2012) - Johnson, Claire E; Lizama, Natalia; Garg, Neeraj; Ghosh, Manonita; Emery, Jonathan; Saunders, Christobel
Abstract Aim To investigate general practitioners' (GPs) preferences for involvement in the management of people diagnosed with the seven most frequent cancers and any barriers to or concerns about an expanded role for GPs. Methods A self‐report survey was mailed to a random sample of 1969 Australian GPs. Results In all, 33% (648) of GPs participated. Participants were a median of 50 years and worked 38 h per week; 53% were male and 68% practiced in metropolitan areas. Most participants preferred to be involved in cancer prevention (86%) and initial diagnosis (85%). Fewer were interested in monitoring for recurrence (70%), follow up after treatment (68%), coordinating psychological support (70%) and palliative care (68%). Only 52% of GPs had a preference for providing supportive care to manage the symptoms of cancer treatment, 45% for managing postoperative care and 40% for coordinating treatment. On multivariate analysis, preference for involvement in more aspects of cancer management increased with age (P = 0.030), if the GP practiced in rural compared to metropolitan areas (P = 0.005), was a partner in a practice compared to a sole practitioner (P = 0.003), had previously received cancer‐specific training (P < 0.001) or was interested in future training (P < 0.001). Open responses identified limited time, communication and information transfer between GP and specialists as important barriers to involvement in cancer management. Conclusion While many GPs are currently involved in some aspects of cancer management, with training, good communication and support from specialists this role may be successfully expanded.